Time-restricted eating improves health because of energy deficit and circadian rhythm: A systematic review and meta-analysis - Yuwen Chang; Tingting Du; Xiangling Zhuang; Guojie Ma (iScience, 2024)
Summary: Time-restricted eating (TRE) is an effective way to lose weight and improve metabolic health in animals. Yet whether and how these benefits apply to humans is unclear. This systematic review and meta-analysis examined the effect of TRE in people with overweight and obesity statuses. The results showed that TRE led to modest weight loss, lower waist circumference and energy deficits. TRE also improved body mass index, fat mass, lean body mass, systolic blood pressure, fasting glucose levels, fasting insulin levels, and HbA1c%. Subgroup analysis demonstrated more health improvements in the TRE group than the control group under the ad libitum intake condition than in the energy-prescribed condition. Eating time-of-day advantages were only seen when there was considerable energy reduction in the TRE group than the control group (ad libitum condition), implying that the benefits of TRE were primarily due to energy deficit, followed by alignment with eating time of day.